Business News and Business Cycles - Bybee, Leland,Kelly, Bryan T.,Manela, Asaf,Xiu, Dacheng (National Bureau of Economic Research, 2021)
We propose an approach to measuring the state of the economy via textual analysis of business news. From the full text of 800,000 Wall Street Journal articles for 1984-2017, we estimate a topic model that summarizes business news into interpretable topical themes and quantifies the proportion of news attention allocated to each theme over time. News attention closely tracks a wide range of economic activities and explains 25% of aggregate stock market returns. A text-augmented VAR demonstrates the large incremental role of news text in modeling macroeconomic dynamics. We use this model to retrieve the narratives that underlie business cycle fluctuations
10.3386/w29344
Keywords: Arbeitspapier; Graue Literatur; Mediale Berichterstattung; Zeitung; Ankündigungseffekt; Frühindikator; Konjunktur; Börsenkurs; Rendite; VAR-Modell; USA; stock market return